Implementasi Strategi Digitalisasi dan Rebranding pada Usaha Mikro - Nehemiah Andrew Wiliatno; Verian Jonathan Handoko; Widjaja, Vincentius Alexander; Sesilya Kempa (Yayasan Literasi Sains Indonesia, 2026)
This Community Service activity aims to assist Depot Oemah Mie in improving performance and competitiveness with a focus on strengthening branding, digital marketing, financial management, and improving customer experience. The approach used is descriptive with a case study survey method to collect primary data through observation, interviews with owners and consumers, and visual documentation. The situation analysis showed great potential in digital marketing optimization and spatial arrangement to create a more attractive atmosphere for customers. The interventions include updating the design of the banner, logo, and menu to be more in line with the trend and character of the product. In addition, marketing management through social media, especially Instagram, was done more effectively to increase the visibility of Depot Oemah Mie. A more open and comfortable space arrangement also has a positive impact on customer comfort. To simplify transactions and improve financial management, the use of the QRIS system was implemented. The results of this activity show improvements in the aspects of branding, digital marketing, spatial arrangement, and financial management that support the sustainability of Depot Oemah Mie's business.